Arthropod community at different altitudes in Gunung Halimun-Salak National Park, Western Java, Indonesia - NOOR FARIKHAH HANEDA; IWAN HILWAN; EWI IRFANI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Haneda NF, Hilwan I, Irfani E. 2019. Arthropod community at different altitudes in Gunung Halimun-Salak National Park, Western Java, Indonesia. Biodiversitas 20: 1735-1742. Gunung Halimun Salak National Park (GHSNP) stores high biodiversity both from its flora and fauna. Parts of the diversity that have not been widely explored are soil arthropods at different altitudes. The aim of this study was to analyze soil arthropod community and the correlation between the attributes of soil arthropods and the environmental factors. The soil arthropods were collected using pitfall traps, placed in several altitudes, i.e., 500 m, 700 m, 900 m, 1100 m, 1300 m, 1500 m, and 1700 m . The attributes of community and environmental parameters were analyzed using Pearson correlation and principal component analysis. The result showed that family Formicidae dominated the soil arthropod community. The diversity of arthropods increased with increasing altitudes. The habitat at the altitudes of 1500 m, 1300 m and 1100 m had a dense canopy, thick litter and high total N and organic C. There was positive correlation between the attributes of soil arthropod community and environment variables.